Direction of wording and responses to items in oral health-related quality of life questionnaires for children and their parents - Locker D, Jokovic A, Allison P (Blackwell Synergy, 2007)
In order to minimize acquiescence response set bias, it is often recommended that questionnaires measuring attitudes, behaviours or health states contain items worded positively and negatively.